Genome‐wide association analysis of resistance to Pythium ultimum in common bean (Phaseolus vulgaris). (19th August 2020) - Dramadri, Isaac Onziga; Amongi, Winnyfred; Kelly, James D.; Mugisha Mukankusi, Clare
Abstract: Pythium root rot (PRR) caused by Pythium spp. is an important root rot disease affecting common bean productivity. The objective of this study was to conduct a genome‐wide association analysis of resistance to PRR in the common bean of Andean gene pool using single nucleotide polymorphism (SNP) markers. About 260 genotypes of the Andean diversity panel (ADP) were evaluated under screen house conditions using Pythium ultimum isolate MS61 in Uganda. Sixteen significant signals for resistance to PRR were detected on chromosomes Pv01, Pv02, Pv04, Pv05 and Pv09 using 260K GBS‐based and 6K Beadchip SNPs. Common significant signals were detected on Pv02 and Pv09 for PRR. Positional candidate genes associated with significant SNPs on Pv02 were Phvul.002G119700, 16.97 kb near marker S02_25507837 (25.50 Mb), encoding Subtilase family protein, and Phvul.002G278400 near marker ss715645959 (44.79 Mb) encoding Defensin‐like (DEFL) protein involved in plant defence responses. Based on the relatively high heritability estimates observed for PRR in this study, significant SNP markers associated with genomic regions for resistance to PRR could be validated for marker‐assisted breeding in Andean beans.